Inventories and the Business Cycle: An Equilibrium Analysis of ( S, s ) Policies - Khan, Aubhik; Thomas, Julia K (American Economic Review, 2007)
We develop an equilibrium business cycle model where nonconvex delivery costs lead firms to follow (S, s) inventory policies. Calibrated to postwar US data, the model reproduces two-thirds of the cyclical variability of inventory investment. Moreover, it delivers strongly procyclical inventory investment, greater volatility in production than sales, and a countercyclical inventory-to-sales ratio. Our model challenges several prominent claims involving inventories, including the widely held belief that they amplify aggregate fluctuations. Despite the comovement between inventory investment and final sales, GDP volatility is essentially unaltered by inventory accumulation, because procyclical inventory investment diverts resources from final production, thereby dampening fluctuations in sales. (JEL E22, E32).